The Reconstruction of Reality in Theaters of Operations by War Correspondents: Array - Mireanu, Constantin (Acta Universitatis Danubius. Communicatio, 2021)
There are many studies in specialized literature that refer to media effects, how the press influences public opinion, how journalists choose to frame a particular topic, sometimes intentionally, in order to achieve an immediate effect, other times because it is fashionable, for the sake of rating, or following firm orders received from the newsroom. However, in crisis situations, the way information is accomplished, the accuracy of the information, its subjectivity, or the shallowness of the articles can have serious consequences and can directly influence the course of military operations. The purpose of this approach is far from throwing this risky, attractive, complicated journalistic genre into ridicule, but rather to try to understand some of the mechanisms underlying the construction of reality in the media and to invite readers to be more careful when consuming media products other than as mere entertainment. Therefore, in this article, we will explore what is and how the reconstruction of reality in theaters of operations through war correspondents occurs under the impact of the phenomenon of searching for the sensational on the battlefield. “This paper was financially supported by the Human Capital Operational Program 2014-2020, co-financed by the European Social Fund, under the project POCU/380/6/13/124708 no. 37141/23.05.2019, with the title “Researcher-Entrepreneur on Labour Market in the Fields of Intelligent Specialization (CERT-ANTREP)”, coordinated by the National University of Political Studies and Public Administration.” “This paper was elaborated within the Human Capital Operational Program 2014-2020, co-financed by the European Social Fund, under the project POCU/380/6/13/124708 no. 37141/23.05.2019, with the title “Researcher-Entrepreneur on Labour Market in the Fields of Intelligent Specialization (CERT-ANTREP)”, coordinated by the National University of Political Studies and Public Administration.”